High‐resolution imaging of the actin cytoskeleton and epithelial sodium channel, CFTR, and aquaporin‐9 localization in the vas deferens. Issue 2 (17th January 2020) - Sharma, Sachin; Kumaran, Girishkumar K.; Hanukoglu, Israel
Abstract: Vas deferens is a conduit for sperm and fluid from the epididymis to the urethra. The duct is surrounded by a thick smooth muscle layer. To map the actin cytoskeleton of the duct and its epithelium, we reacted sections of the proximal and distal regions with fluorescent phalloidin. Confocal microscopic imaging showed that the cylinder‐shaped epithelium of the proximal region has a thick apical border of actin filaments that form microvilli. The epithelium of the distal region is covered with tall stereocilia (13–18 µm) that extend from the apical border into the lumen. In both regions, the lateral and basal cell borders showed a thin lining of actin cytoskeleton. The vas deferens epithelium contains various channels to regulate the fluid composition in the lumen. We mapped the localization of the epithelial sodium channel (ENaC), aquaporin‐9 (AQP9), and cystic fibrosis transmembrane conductance regulator (CFTR) in the rat and mouse vas deferens. ENaC and AQP9 immunofluorescence were localized on the luminal surface and stereocilia and also in the basal and smooth muscle layers. CFTR immunofluorescence appeared only on the luminal surface and in smooth muscle layers. The localization of all three channels on the apical surface of the columnar epithelial cells provides clear evidence that these channels are involved concurrently in the regulation of fluid and electrolyte balance in the lumen of the vas deferens. ENaC allows the flow of Na + ions from the lumen into the cytoplasm, and the osmotic gradient generated provides the driving force for the passive flow of water through AQP channels.